Penggunaan Abu Jerami Padi dan Pupuk N Pada Bibit Kelapa Sawit (Elaeis guineensis Jacq) di Pembibitan Utama - Yuliyatun, Yuliyatun; Nelvia, Nelvia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to study the effect of the use of straw ash of rice and N ferilizer on palm oil seedling in main nursery. The research conducted at the garden of the experiment faculty agriculture of the university of Riau from April until August 2015.  The research in form experiment of factorial 3 x 3 arranged in completely randomized design. The first factor was straw ash of rice consist of 3 level (0, 5, 10 g/10 kg of soil) and the second factor was N fertilizer consist of 3 level (0, 0.7, 1.4 g/10 kg of soil), each combination of treatment was repeated 3 times. Parameter that examined is high plant, number of leaves, the diameter of excrescence, volume of roots, the ratio of roots headrer,  and weight of dried seeds palm oil. The results showed that the straw ash of rice dose 5 g/10 kg of soil and N fertilizer 1.4 g/10 kg of soil increased the high plant, volume of roots, and weight of dried seeds palm oil compared to another treatment and without treatment. The increased straw ash of rice from 5 g/ 10 kg of soil to 10 g/10 kg of soil tended to reduce high plants, the diameter of excrescence, volume of roots, ratio of roots headrer, and weight of dried seeds palm oil.  The results dose of N fertilizer until 1.4 g/10 kg of soil increased high plants, volume of roots seeds, and ratio of roots headrer seeds palm oil. Keywords : palm oil, straw ash of rice, N fertilizer